2005
DOI: 10.1111/j.1365-201x.2004.01400.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of different air velocities on heat storage and body temperature in humans cycling in a hot, humid environment

Abstract: The finding of previous laboratory studies showing a beneficial effect of high rates of fluid ingestion on thermoregulation during exercise in hot, humid, windstill conditions cannot be extrapolated to out-of-doors exercise in which facing air velocities are seldom lower than the athlete's rate of forward progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
128
3
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(140 citation statements)
references
References 50 publications
4
128
3
2
Order By: Relevance
“…However, T sk was elevated at 2.8 m/s. 33 Therefore, with a more appropriate air velocity in our study, skin temperature and body temperature probably would have been lower in both conditions, and this might have reduced the efficacy of our intervention. Further research is needed to test the efficacy of our intervention in laboratory studies using more realistic air velocities or studies undertaken in the field.…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, T sk was elevated at 2.8 m/s. 33 Therefore, with a more appropriate air velocity in our study, skin temperature and body temperature probably would have been lower in both conditions, and this might have reduced the efficacy of our intervention. Further research is needed to test the efficacy of our intervention in laboratory studies using more realistic air velocities or studies undertaken in the field.…”
Section: Future Directionsmentioning
confidence: 99%
“…Saunders et al 33 reported that core temperature, heart rate, sweat rate, and perceived exertion were not different between air velocities of 2.8 m/s (9.9 km/h) and the more appropriate 9.3 m/s (33 km/h) during 2 hours of cycling at 60% peak power in a 33°C and 59% relative humidity environment. However, T sk was elevated at 2.8 m/s.…”
Section: Future Directionsmentioning
confidence: 99%
“…Despite this, the two-compartment model is still extensively used for the estimation of ⌬T b and ⌬H b , both as an analytical tool for assessing individual heat load status for a wide range of subpopulations (1,7,36,49) and extensively as a physiological criterion for maximal heat exposure (2,16,17,19,22).…”
mentioning
confidence: 99%
“…The results of the study Saunders et al 15 an increase in BT at a relative humidity of 80% compared with 59% relative humidity to nine subjects after cycling for two hours. This statement was in accordance with the results of research Yashasi et al 16 physical exercise at high relative humidity causes the core body temperature was higher than the low relative humidity.…”
mentioning
confidence: 93%